Review of Creativity and Chaos: Reflections on a Decade of Progressive Change in Public Schools, 1967-1977 by Charles Suhor - Stan Scott (Journal of the Assembly for Expanded Perspectives on Learning, 2022)
In the title of Charles Suhor’s engaging memoir, the words progressive, change, and creativity—even chaos—will I suspect light fires of the imagination for many progressively inclined teachers and other readers. That goes all the more for those of us who lived through the upheavals and exciting breakthroughs of the late ‘60s and ‘70s, who may also have fought battles, like the ones recounted by Suhor, on behalf of our own students and children, to bring progressive changes to schools and colleges. As a former professor of English and philosophy and co-chair (with my friend and colleague Irene Papoulis) of the Assembly for Expanded Perspectives on Learning, I have a special admiration for Charlie Suhor’s work as an educational reformer and his vision as one of the founders of this Assembly of creative teachers and scholars.
Keywords: JAEPL